Photooxidation of blends of vinyl alcohol – vinyl acetate copolymer with polyhydroxybutyrate - V. B. Ivanov; S. I. Voinov; A. A. Olkhov; M. V. Solin; M. A. Goldshtrakh; S. V. Vlasov (Тонкие химические технологии)
The influence of poly(3-hydroxybutyrate) (10-20 weight %) on the expenditure and accumulation of chromophore groups was studied, as well as oxygen absorption upon photooxidation of a vinyl alcohol - vinyl acetate copolymer. The article suggests a kinetic model of the expenditure and accumulation of functional groups upon photooxidation of the mentioned copolymer and of blends based on it.